The stress and strain of triathlon racing in different thermal environments - Creasy, R. (University of Otago, 2019)
Athletic endurance competitions in hot environments have become more relevant in professional sports. The inception for this thesis was to understand why a group of elite endurance triathletes repeatedly failed to perform in hot environments. The subsequent aims were to explore the physiological basis of elite endurance performance in the heat, with a focus on cerebrovascular responses because they seemed relevant and yet remained relatively less well explored.